2013
DOI: 10.1177/0013124513496457
|View full text |Cite
|
Sign up to set email alerts
|

“You’re Moving a Frickin’ Big Ship”

Abstract: Scholars have become more attentive to lesbian/gay/bisexual/transsexual/queer/questioning (LGBTQ) topics as queer perspectives become increasingly prevalent in middle and high school environments. This study examines how educators navigate social and academic environments in order to incorporate inclusive pedagogical practices and cultivate safe schools for LGBTQ students. Tenets of structuration theory and heteronormativity are used to analyze interview data in order to unveil the heteronormative structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…Grace (2006) concurs that teachers must first study their own lives, and the intersection of their personal values and beliefs and their professional practice, to better understand how they profoundly impact students' lives and It is critical to underscore that it is unfair to place all of the ownership and blame on classroom teachers, but rather, consider the system in which teachers operate and the level of support they perceive they have or would have to engage in these controversial conversations. This aligns with findings from Fredman et al (2015) and Meyer, Taylor, and Peter (2015), that teachers may avoid this topic out of concern for a lack of administrative backing. Without these conversations from the top down, it is unreasonable to expect teachers to take a leap of faith and hope they will have administrative backing and support if they do open up the classroom space to these critical dialogues.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Grace (2006) concurs that teachers must first study their own lives, and the intersection of their personal values and beliefs and their professional practice, to better understand how they profoundly impact students' lives and It is critical to underscore that it is unfair to place all of the ownership and blame on classroom teachers, but rather, consider the system in which teachers operate and the level of support they perceive they have or would have to engage in these controversial conversations. This aligns with findings from Fredman et al (2015) and Meyer, Taylor, and Peter (2015), that teachers may avoid this topic out of concern for a lack of administrative backing. Without these conversations from the top down, it is unreasonable to expect teachers to take a leap of faith and hope they will have administrative backing and support if they do open up the classroom space to these critical dialogues.…”
Section: Discussionsupporting
confidence: 85%
“…As previously discussed, many teachers routinely omit or avoid topics pertaining to sexual and gender diversity in their class; however, research has supported that this operates more at a systemic level than an individual one. In their qualitative study involving interviews with sixteen educators, Fredman, Schultz, and Hoffman (2015) found teachers avoided topics of homosexuality primarily out of fear of backlash. Their study demonstrated the apprehension of educators about administrative responses as well as repercussion from the community, and parents.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While music educators appear receptive to teaching trans 1 students (Silveira & Goff, 2016), students in this population report ongoing discrimination and marginalization at school (Kosciw, Greytak, Giga, Villenas, & Danischewski, 2016). Educators who do not understand the expanding gender spectrum may feel uncomfortable or unprepared to teach students with whom they share little or no common ground about gender diversity (e.g., Fredman, Schultz, & Hoffman, 2015). A teacher who has limited knowledge of the social construct of gender might make policy and curricular decisions that lack openness or affirmation for individuals who do not identify within the gender binary.…”
mentioning
confidence: 99%
“…Throughout education research on LGBTQ inclusion, scholars have found that school systems and individual educators alike are willing to engage with gender and sexuality diversity to the degree that the conversation is about safety and tolerance (see, for instance, Bower & Klecka, 2009; Formby, 2015; Fredman et al, 2013; Payne & Smith, 2012, 2018; Smith, 2018; Ullman, 2018). These are the discursive frames that are typically used to acknowledge nondominant identities in K–12 settings and define the scope of a school’s responsibility to make school a place where a diverse population can complete an education.…”
Section: Discomfort As Controlmentioning
confidence: 99%